Biofertilizer from West Kalimantan Seaweeds and Its Trialson Alluvial Soils - Pramono Putro Utomo (Biopropal Industri, 2012)
Coastal areas of West Kalimantan province are rich with seaweed. To increase its economic value, seaweed could be used as primary materials for organic fertilizer production. This research was conducted to find the optimum combination of seaweeds used for organic fertilizer production using Brassica rapa as test plant on alluvial soils. Most dominant seaweeds found were used for biofertilizer production. Three types of seaweeds used were brown (Phaeophyceae), red (Rhodophyceae), and green (Chlorophyceae). Formulations used were 1:1:1, 1:1:2, 1:2:1, and 2:1:1. The formulation that met the biofertilizer quality conformance was applied on alluvial soils using Brassica rapa as a test plant. Result showed that 2:1:1 and 1:2:1 ratio of brown-red-green seaweed is the best formulation based on most growth parameters observed on Brassica rapa.